Development of Teaching Materials of Flat Side Spaces Building Based on Problem Based Learning with Assemblr Assistance to Improve Students' Spatial Ability (Department of Mathematics, Universitas Negeri Semarang, 2022)
This study aims to develop teaching materials for flat-side space buildings based on problem-based learning assisted by Assemblr to improve students' spatial abilities. The method used was Research and Development with a 4D development model modified to 3D, namely: define, design, and develop. The last stage (dissemination) was not carried out due to the limitations of energy, cost, time, and deployment space of the researcher. The data collection technique used a questionnaire, which consists of a feasibility test and a readability test. The results of the feasibility test obtained a percentage of 89% meaning that teaching materials were declared suitable for use in learning. The readability test results obtained a percentage of 87% meaning that the teaching materials were declared easy for students to understand. The results of the study obtained teaching materials that are valid and suitable for use in learning and are easy to understand by readers.